2007
DOI: 10.1007/s10823-007-9051-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depression in Aging South Asian Canadians

Abstract: This study examined the prevalence and factors of depression among aging South Asians in Canada. Telephone surveys were conducted with a random sample of aging South Asians aged 55 and above. Hierarchical regression analysis was used to determine the factors of depression, which was measured by an adapted 15-item Geriatric Depression Scale. Over one in five (21.4%) participants reported at least a mild level of depression. A stronger agreement with South Asian cultural values was significantly related to a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 109 publications
2
60
0
Order By: Relevance
“…It was measured by asking the caregivers to report either yes (1) or no (0) to a list of 15 health problems or illnesses that are commonly used in different health and caregiving studies on different aging populations (Lai, 2007a;Lai & Surood, 2008;Lai, Tsang, Chappell, Lai, & Chau, 2007). A higher score represented more health problems or diseases.…”
Section: Methodsmentioning
confidence: 99%
“…It was measured by asking the caregivers to report either yes (1) or no (0) to a list of 15 health problems or illnesses that are commonly used in different health and caregiving studies on different aging populations (Lai, 2007a;Lai & Surood, 2008;Lai, Tsang, Chappell, Lai, & Chau, 2007). A higher score represented more health problems or diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on health conditions, the mental health of aging populations may be either aggravated or mitigated. Prior studies have demonstrated that physical health is an important predictor of depression in older age among the general population (Falcón & Tucker, 2000), and among Asian immigrant elders, specifically in New York City and Boston (Mui, 1996;Wu, Tran, & Amjad, 2004), and in small cities in the United States and Canada (Lai & Surood, 2008;H.-Y. Lee et al, 1996).…”
Section: Stress and Coping Theorymentioning
confidence: 99%
“…A Karachi based study on prevalence of depression by type of family system and correlation of depression with other important sociodemographic variables found nuclear family system, female sex, a low level of education, single/widowed /divorced, living alone and being childless were the factors related to depression [22]. A study by Lai DWL & Surood S [23] examined the linkages between socio-cultural factors and depression in older South Asians in Canada which suggested that the mental health interventions should consider the cultural uniqueness of that target population and the service delivery system should ensure that services are known and accessible to the increasingly culturally diverse aging population. Physical illnesses, disability, pain and psychosocial variables were also found to be closely related to the symptoms of depression [24].…”
Section: Diagnostic and Statistical Manual Of Mental Disorders [Dsm Imentioning
confidence: 99%